(untitled) (Zaporizhzhia Historical Review, 2021)
In the article the attempt to consider some aspects of the public life of German ethnos in Ukraine, on the basis of the newest historical material is made, The greater consolidating and educational role of the church in the sphere of development of German national ethnos is determined.